The natural history of shrimp hypersensitivity - Daul, Carolyn Beach; Morgan, Jane E.; Lehrer, Samuel B. (Journal of allergy and clinical immunology, 1990)
Sera collected sequentially during a 24-month interval from 11 individuals with shrimp hypersensitivity and 10 nonhypersensitive control subjects were evaluated for shrimp-specific IgE, IgG, IgM, and IgA reactivity. Shrimp-hypersensitive subjects underwent double-blind, placebo-controlled shrimp challenges; seven exhibited positive challenges, and four subjects reported the subjective symptom of oropharyngeal pruritus. Shrimp-specific IgE levels in all subjects were relatively constant during the 24 months of this study and not affected by shrimp challenge, although some fluctuation in the shrimp-specific IgG, IgM, and IgA reactivity were noted, apparently unrelated to shrimp. challenge. Shrimp-specific IgE and IgG, but not IgM and IgA, were significantly higher in the group with shrimp hypersensitivity as compared to the control subjects. Moreover, the challenge-positive subjects had higher levels of both shrimp-specific IgE and IgG than subjects reporting pruritus. The levels of shrimp-specific IgG correlated directly with shrimp-specific IgE reactivity. These studies indicate that serum levels of shrimp-specific IgE are significantly elevated in shrimp-hypersensitive subjects who exhibit positive food challenges, and these baseline levels did not appear to be altered long term by isolated shrimp challenge. Furthermore, baseline shrimp-specitif antibody (IgG, IgM, and IgA) levels noted in normal subjects were not markedly affected by frequent ingestion of shrimp.